IMPROVING STUDENTS LISTENING COMPREHENSION BY USING BOTTOM-UP TECHNIQUE - Akbar, Hari Razaki; Maral, Sofian; Wardah, Wardah (FKIP - Universitas Tanjungpura, 2020)
The aim of this research was to improve students listening comprehension by using Bottom-Up technique. This research is a classroom action research which has done in three cycles. The subject for this research was the tenth grade students in class X TAV. The research was conducted by using Bottom-Up technique which consists of three main stages. There are word processing, phrase processing, and comprehension. The researcher observed students improvement in listening comprehension by collecting data through field notes, observation checklist and listening test. Field note and observation checklist were used to gather the students attitude in learning process. The data of listening was collected through listening test and it was assessed through scoring rubric. The result showed that students problems in understanding the contents of listening and vocabulary had been solved by using Bottom-Up technique. In the first cycle, the students mean score was 76.7. It increased in the second cycle to 82.1, and 83.7 in third cycle. As the conclusion, the technique was able to be used in improving students listening comprehension. The researcher recommends the teacher to use Bottom-Up technique as a technique in teaching and learning process, especially in the teaching listening with the similar setting and difficulty.